PROSES PEMBUATAN DAN UJI KARAKTERISTIK BIOETANOL DARI KULIT NANAS (ANANAS COMOSUS) - Kahar, Abdul; Fathoni, Rif'an; Ardiah, Rida; Mulyani, Nunuk (Universitas Mulawarman, 2025)
Bioethanol is one solution to reduce the exploitation of fossil energy produced from biomass fermentation. Bioethanol production can be done from starchy plants or those containing carbohydrates, glucose and cellulose. One of them is pineapple skin, pineapple skin is fruit waste which has quite high sugar and carbohydrate content. The Central Statistics Agency (BPS) reports that pineapple production in Indonesia will reach 2.89 million tons in 2021. This number grew 17.89% compared to the previous year which amounted to 2.45 million tons. The process of making bioethanol begins with preparation, hydrolysis, fermentation, distillation and FTIR analysis. The hydrolysis process uses acid hydrolysis using hydrochloric acid (HCL) and the best hydrolysis is obtained at a temperature of 100 C to produce the highest sugar content, namely 17% Brix. The fermentation process using saccaromyces cerevisiae yeast for 14 days with pH control under acidic conditions, namely 4-5 yeast gnats used can work optimally. The alcohol content after distillation was found to be >80. The FTIR test showed that there was ethanol in the bioethanol sample from pineapple skin.